Європейська інтеграція України: сучасний стан та перспективи - Рудянин, Іван Петрович; Rudianyn, Ivan P. (Чернівецький національний університет імені Юрія Федьковича, 2015)
The article considers the prospects for Ukraine's entry into the European Union. Highlighted the key areas of government business, are subject to reform. Indicated, how important is understanding by the population in needing of reforms that will facilitate the integration of Ukraine into the European space.
Keywords: Європейський Союз; Україна; євроінтеграція; Угода про асоціацію з Європейським Союзом; European Union; Ukraine